Respuesta :

Answer:

By graphing ; [tex]\log_2 (x-1) = \log_{12} (x-1)[/tex] only for x =2

Step-by-step explanation:

Solve: [tex]\log_2 (x-1) = \log_{12} (x-1)[/tex]

let [tex]y_1=\log_2 (x-1)[/tex] and [tex]y_2=\log_{12} (x-1)[/tex]

To find the x for which [tex]y_1= y_2[/tex]

A graph of these [tex]y_1=\log_2 (x-1)[/tex] and [tex]y_2=\log_{12} (x-1)[/tex] shows us that the graph intersect.

This implies that there is a single (x, y) value that satisfies both equations.

i.,e (2, 0)

Therefore,  [tex]\log_2 (x-1) = \log_{12} (x-1)[/tex] only when x =2

You can see the graph as shown below:

Ver imagen OrethaWilkison

Answer:

x=2

Step-by-step explanation: